Tata Kelola Pengembangan Kurikulum Sains Qurani di Lembaga Yayasan Pendidikan Islam - Kholishotul Amaliyah; Irawan Irawan; Tedi Priatna (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The problem of this research is related to how the development of the educational curriculum shapes the competence of students' spiritual attitudes, so that the learning curriculum becomes a means to increase faith and piety. The Madrasah that has implemented an Al-Qur'an-based science integration curriculum is the Islamic Education Foundation MTs Science Qurani Azzakiyyah, Cinunuk Village, Cilenyi District, Bandung Regency. This study uses qualitative research with observational research techniques, interview data and reference documentation study data. The results showed that the integration of the Al-Qur'an-based science curriculum greatly influenced the awareness of students' spiritual attitudes in learning science, besides that, students were more motivated to research, study and open insights about scientific cues in the Al-Qur'an . The efforts that have been made by the Azzakiyyah Islamic Education Foundation continue to be refined and enriched as well as collaboration with various professional institutions. This program is very strategic to be developed in a wider scope, especially in Islamic educational institutions and Madrasahs which have the same vision and mission to foster awareness of monotheism in learning in accordance with the ideals of a fully Islamic education. Keywords: Integrity, Science Curriculum Development, Al-Qur'an Based